Philippines : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses the findings of Fiscal Transparency Evaluation on Philippines. Improving fiscal transparency has been a priority in the Philippines over recent years. The government's public financial management reform strategy has helped initiate a wide variety of reforms, which are beginning to bear fruit. Fiscal reporting is relatively comprehensive, frequent, and timely, with many areas of good and advanced practices. Fiscal risk analysis and management is relatively strong in the Philippines compared with other countries. However, improvements are needed in a few areas, especially to capture of risks from guarantees and public-private partnership, assess the scope of tax expenditures, and introduce a longer-term perspective in the fiscal sustainability analysis.